Adherence to statin treatment and readmission of patients after myocardial infarction: a six year follow up study. Issue 3 (1st September 2002) - Wei, L; Wang, J; Thompson, P; Wong, S; Struthers, A D; MacDonald, T M
Abstract : Objective: To investigate patients' adherence to statin treatment prescribed following their first myocardial infarction (MI) and to estimate the effect of adherence to statins on recurrence of MI and all cause mortality. Design: Cohort study using a record linkage database. Setting: Tayside, Scotland, UK. Patients: Patients who experienced their first MI between January 1990 and November 1995. Main outcome measures: Percentage of statin use and adherence to statins by patients after an MI and the relative risk of hospitalisation for recurrent MI. The effect of adherence on all cause mortality was also examined. The covariates used were age, sex, socioeconomic deprivation, serum cholesterol concentration, diabetes mellitus, cardiovascular drug use, and other hospitalisations. Results: Of 5590 patients who experienced an incident MI, 717 (12.8%) experienced at least one further MI. Only 7.7% of patients used statins after an MI during the study period. Compared with those not taking statins, those who had 80% or better adherence to statin treatment had an adjusted relative risk of recurrent MI of 0.19 (95% confidence interval (CI) 0.08 to 0.47) and all cause mortality of 0.47 (95% CI 0.22 to 0.99). There was no significant reduction in either end point for those who were less than 80% adherent to statins. Conclusions: Despite the infrequent use of statin during the study period, good adherence to statin treatment was associated with lower risk of recurrent MI.